Flow-oriented Venous Anastomosis to Control Lymph Flow of Lymphatic Malformation. Issue 7 (July 2019) - Kato, Motoi; Watanabe, Shoji; Watanabe, Azusa; Iida, Takuya
Abstract : Background: Less-invasive surgeries, such as lymphaticovenular anastomosis (LVA), are the widely accepted intervention for lymphedema. This study aimed to assess the outcomes of flow-oriented LVA modification on lymphatic malformation (LM). Methods: We included 19 patients diagnosed with LM mixed type or microcystic type, who came to our clinic from June 2015 to December 2017. Under general anesthesia, all patients were administered an indocyanine green lymphography injection subcutaneously. In the case of a strong inflow, the patient underwent afferent lymph vessel of LM to venous anastomosis (LMVA). Otherwise, the side wall of LMVA was performed to the cysts. Outcomes were classified into the following groups based on the size changes: treatment effect (TE) 4 = >80% reduction rate; TE 3 = 50%–80% reduction rate; TE 2 = 20%–50% reduction rate; and TE 1 = 0%–20% reduction rate. Results: All cases underwent surgery, with no case having an increased size. The results were as follows: TE 4 = 4 (21%) patients; TE 3 = 6 (32%) patients; TE 2 = 5 (26%) patients; and TE 1 = 4 (21%) patients. No case required study termination due to disease progression. Minor complication occurred in 3 cases. One vesicle increased at the labial mucosa and one wound dehiscence that epithelized within 1 month. Conclusion: LMVA could be a novel, minimally invasive lymph flow-oriented surgical method for intractable LM.